Digital preservation strategy of institutional repository in Malaysian research universities / Imilia Ibrahim - Ibrahim, Imilia (2022)
The establishment of the institutional repositories in Malaysian research universities begins in 2007. The main purpose of the institutional repository development is for the enhancement of the visibility of the universities’ knowledge output. As the institutional repositories store and manage the knowledge output created in digital forms, the sustainability of the collections may be at risks due to the complexity and the rapid development of the digital environment. This study is meant to investigate the implementation of the digital preservation strategy among the institutional repositories in the Malaysian research universities. Furthermore, the study would explore the inhibiting factors that would affect the implementation of the digital preservation strategy by the institutional repositories. This study implemented qualitative methods to gain a holistic perspective on how the institutional repository plan and manage their digital collections and their operational and technical approach towards digital preservation strategy. The methodologies applied for the data collections include desktop review, which would collect and analyse data from the contemporary digital preservation strategy documents in order to build a framework for the digital preservation strategy and as a guide for the researcher to further investigate the implementation of the digital preservation strategy within the institutional repository and the inhibiting factors faced by the institutional repository through semi-structured interviews, and observations. The findings from the study were translated into a framework developed for digital preservation strategy meant for institutional repository in Malaysian research universities. The study on the digital preservation strategy implementation by institutional repository in Malaysia would be the first to utilize the desktop review methodology. It is hoped that the study would contribute to the better administration and sustainability of digital collections in Malaysian research universities and would be a benchmark for other institutions involved in managing digital collections in the nation.